How to talk about love in war. A reading of the passionate polarities in The Art of War by Nicholas Machiavelli - Mattei, Eugenia (Las Torres de Lucca. International Journal of Political Philosophy, 2022)
The aim of this article is to analyze the presence of the polar passions in Machiavelli’s The art of war. First, there is a brief analysis of Ambrogio Lorezetti’s frescoes in the town hall in Siena, focusing on the presence of war and peace so as to then move on to a comparative analysis of Machiavelli’s approach. Second, there is an exploration of how the scholarly articles analyze this military treatise by Machiavelli. Third, the references to love in the game of polar passions which appear throughout the text are studied from two perspectives: on the one hand, the explicit references to love in the form of love of one's homeland and love of peace; and on the other hand, how the passion of love in the passionate circuit between a captain and his troop appears.
Keywords: conflict; harmony; passions; peace; war